Effective demand, local governments and economic growth in post-Mao China: A spatial econometrics perspective - Yongbok Jeon (The University of Utah, Department of Economics, 2008)
The purpose of this study is to empirically test the validity of Kaldor's laws of economic growth in China between 1978 and 2004 and to provide an alternative explanation of sources of Chinese economic growth in a Kaldorian perspective. First, in a spatial econometrics perspective using a regional data set, the present paper empirically verifies that Kaldorian hypotheses on economic growth hold in China during the sample period. Second, it suggests the empirical findings as proving the validity of a demand-side approach. Third, taking this implication, this study provides a more detailed alternative explanation of the sources and processes of economic growth in China during the sample period. Finally, considering a striking finding of the lack of spatial (regional) dependence among Chinese provinces, it also discusses the role of local governments in the development process in China. This study is expected to contribute to the literature as being one of the first studies that identifies sources of Chinese economic growth in demand side.
Keywords: O11; O14; O53; R58; 330; economic growth in China; Kaldor's laws; effective demand; Chinese local governments